Dear Congress participant, student and colleague! (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
On behalf of the Department of Social Sciences of the National Academy of Sciences of the Kyrgyz Republic, I heartily congratulate you on the publication of the collection of materials for the International Congress «Traditional Culture and Art: Problems of Preservation and Development», which is held as part of the World Festival of Traditional Culture and Music «Ruh Sanat»!
Keywords: -